Comparative Analysis of Professional Characteristics of Internet Addiction Formation - Ghazaryan, Lusine (Bulletin of Yerevan University E: Philosophy, Psychology, 2025)
In this article, we examined the influence of professional activity on the development of Internet addiction based on psychological theories and a comparative analysis of surveys and testing of specialists. In the article, we examined the influence of the features of professional activity on the formation of Internet addiction based on comparative analysis and psychological theories. In the digital age, the use of the Internet has become an integral part of life, significantly changing our work, educational and social environment. At the same time, excessive Internet use leads to Internet addiction, which is currently considered an urgent problem of psychological and social health. This problem is especially relevant in the professional environment, where the work efficiency and mental health of employees are closely linked to digital technologies. The study of Internet addiction has been gaining momentum in recent years, but the specifics of addiction formation in the professional environment and its impact have not yet been studied deeply enough. The article is devoted to Internet addiction in various professions․